Hamster organotypic kidney culture model of early-stage SARS-CoV-2 infection highlights a two-step renal susceptibility. (September 2022) - Shyfrin, Sophie R; Ferren, Marion; Perrin-Cocon, Laure; Espi, Maxime; Charmetant, Xavier; Brailly, Manon; Decimo, Didier; Iampietro, Mathieu; Canus, Lola; Horvat, Branka; Lotteau, Vincent; Vidalain, Pierre-Olivier; et al.
Kidney pathology is frequently reported in patients hospitalized with COVID-19, the pandemic disease caused by the Severe acute respiratory coronavirus 2 (SARS-CoV-2). However, due to a lack of suitable study models, the events occurring in the kidney during the earliest stages of infection remain unknown. We have developed hamster organotypic kidney cultures (OKCs) to study the early stages of direct renal infection. OKCs maintained key renal structures in their native three-dimensional arrangement. SARS-CoV-2 productively replicated in hamster OKCs, initially targeting endothelial cells and later disseminating into proximal tubules. We observed a delayed interferon response, markers of necroptosis and pyroptosis, and an early repression of pro-inflammatory cytokines transcription followed by a strong later upregulation. While it remains an open question whether an active replication of SARS-CoV-2 takes place in the kidneys of COVID-19 patients with AKI, our model provides new insights into the kinetics of SARS-CoV-2 kidney infection and can serve as a powerful tool for studying kidney infection by other pathogens and testing the renal toxicity of drugs.